Pengaruh persepsi korupsi dan kepercayaan kepada pemerintah terhadap tax morale: Peran mediasi pengetahuan perpajakan - Duwi Riningsih (Keberlanjutan)
This study aims to analyze the influence of corruption perception and trust in the government on the tax morale of MSME taxpayers in Kota Kediri, with tax knowledge as an intervening variable. A quantitative method was applied using the Partial Least Squares (PLS) approach to process data from 100 MSME respondents. The results show that corruption perception has a positive and significant effect on tax morale, while trust in the government also has a positive but relatively small influence on tax morale. Tax knowledge emerged as the most significant variable affecting tax morale and strengthened the relationship between trust in the government and tax morale. However, corruption perception did not significantly affect tax knowledge. This study highlights the importance of transparency, tax education, and improved government accountability to create a more inclusive tax system and enhance taxpayer compliance.